Asuhan Keperawatan Pada Pasien Tn. T Dengan Diagnosa Medis Stroke Hemoragik - Nur Azmi, Nadila; Wahyuni, Uni; Wulandari, Afni; Puspitasari, Melati; Risdiyanto, Nugeraha (Awatara Publisher, 2024)
Hemorrhagic stroke is caused by bleeding into the brain tissue (intracerebral hemorrhage) and the space around the brain. This condition causes sufferers to experience sudden severe headaches, decreased level of consciousness, increased intracranial pressure, and neurological deficits such as hemiplegia, hemiparesis, aphasia, and apraxia. The aim of this study was to describe nursing care for Mr. T patients with a medical diagnosis of hemorrhagic stroke in the Teratai room at Waled Hospital, Cirebon Regency. This type of research uses a qualitative approach with case studies as the main method. The subject is Mr. T. The case study was conducted in the Teratai Room at Waled Hospital, Cirebon Regency from 30 November 2023 to 02 December 2023. The data collection methods used were through observation, interviews and analysis of documents such as patient medical records. The nursing problems that arise in this case are ineffective breathing patterns, decreased intracranial adaptive capacity, impaired physical mobility, risk of impaired skin/tissue integrity. The conclusion of the research was that after 3 days of treatment, the nursing problem of ineffective breathing patterns, decreased intracranial adaptive capacity, and impaired physical mobility had not been resolved so the intervention was still continued, while the nursing problem of risk of skin/tissue integrity disorders was partially resolved so that the intervention was still continued as stated. has been planned.